Clinico-Radiological Correlation in 26 Egyptian Children with Glutaric Acidemia Type 1 - Sadek, Abdelrahim A.; Aladawy, Mohammed A.; Magdy, Rofaida M.; Mansour, Tarek M. M.; Othman, Amr A.; Hawary, Bahaa; Ibrahim, Mohamed F.; Hassan, Mohammed H.; Abdelkreem, Elsayed (Neuropediatrics, 2021)
Background Glutaric acidemia type 1 (GA1) is an inherited neurometabolic disease with significant morbidity. However, neuro-radiological correlation is not completely understood.Objective The study aimed to characterize the neuroimaging findings and their association with neurological phenotype in GA1 children.Methods Twenty-six Egyptian children (median age = 12 months) diagnosed with GA1 underwent clinical evaluation and brain magnetic resonance imaging (MRI). We objectively assessed the severity of neurological phenotype at the time of MRI using movement disorder (MD) and morbidity scores. Evaluation of brain MRI abnormalities followed a systematic and region-specific scoring approach. Brain MRI findings and scores were correlated with MD and morbidity scores, disease onset, and presence of seizures.Results Fifteen (57.7%) cases had insidious onset, eight (30.8%) manifested acute onset, whereas three (11.5%) were asymptomatic. Ten (38.5%) cases had seizures, five of which had no acute encephalopathic crisis. Putamen and caudate abnormalities (found in all acute onset, 93.3 and 73.3% of insidious onset, and one of three asymptomatic cases) were significantly related to MD (p = 0.007 and 0.013) and morbidity (p = 0.005 and 0.003) scores. Globus pallidus abnormalities (50% of acute onset, 46.7% of insidious onset, and one of three of asymptomatic cases) were significantly associated with morbidity score (p = 0.023). Other MRI brain abnormalities as well as gray and white matter score showed no significant association with neurological phenotype. Younger age at onset, acute onset, and seizures were significantly associated with worse neurological manifestations.Conclusion Patients with GA1 manifest characteristic and region-specific brain MRI abnormalities, but only striatal affection appears to correlate with neurological phenotype.
Keywords: glutaric acidemia type 1; movement disorder; magnetic resonance imaging; seizures; striatal injury